Leadership talk : a discourse approach to leader emergence - Walker, Robyn. (2013 digital library., 2014)
Takes an in-depth look at an emerging approach to the study of business leadership that focuses on language as a vehicle for communicating leadership. Traditionally, management theories have taken a psychological approach to leadership, often assuming that it is a personality trait located within an individual. In contrast, the discursive approach to leadership, which is the focus of this book, assumes that leadership is created through communication practices. With this understanding, we explore a new definition of leadership as the expression of ideas in talk or in action that are recognized by others as capable of progressing tasks or solving problems. The practical implication of this view of leadership suggests that leaders must constantly enact and communicate their relationship to their followers in such a way as to be recognized by them as a leader. Leadership thus becomes the negotiation that occurs between potential leaders and followers and is thus created in interaction within a particular organizational culture and context rather than residing in the individual. Consequently, leadership becomes the purview of those with excellent analytical skills and communication practices rather than a given personality type. It can be thus be learned and practiced by anyone with the tools to do so.